Incorporation of Turkish Hyalopterus spp. into recent species reassessment based on their molecular and morphometric features - Senol, Özhan; Görür, Gazi (Zootaxa, 2022)
The Hyalopterus group is a Mediterranean originated genus and Turkey is one of the important distribution pathways of the species belonging to this genus. Up to date, Hyalopterus amygdali (from host plant Prunus dulcis), Hyalopterus pruni (from Prunus domestica) and Hyalopterus arundiniformis (from Prunus armeniaca and Prunus persica) are species distinctively defined in Turkey. Samples of Hyalopterus were collected on P. dulcis, P. domestica, P. armeniaca, and P. persica from Afyonkarahisar, Kütahya, Niðde and Uþak provinces from May 2012 to October 2013. To detect morphological variations related with the preferred host plant and locality, 755 individuals’ morphological features were measured. Maximum likelihood and Bayesian analyses of COI (658 bp.) sequences of Hyalopterus spp were applied to evaluate phylogenetic relationships of the genus members. A median joining haplotype network was evaluated to determine the relationships among haplotypes. The molecular and morphometric analyses indicated that the host plant utilization affects the speciation of Hyalopterus spp. There are no comprehensive molecular studies about Hyalopterus in Turkey although previous studies conducted on this genus emphasized the importance of studying the Turkish populations to understand host plant relations, distribution route and speciation of this economically important aphid group. Therefore this study aimed to give information about phylogenetic and morphological variability of Hyalopterus spp. and criticize how these findings are incorporated into the recent species reassesment.